2001
DOI: 10.1523/jneurosci.21-15-05429.2001
|View full text |Cite
|
Sign up to set email alerts
|

Kir4.1 Potassium Channel Subunit Is Crucial for Oligodendrocyte Development andIn VivoMyelination

Abstract: To understand the cellular and in vivo functions of specific K ϩ channels in glia, we have studied mice with a null mutation in the weakly inwardly rectifying K ϩ channel subunit Kir4.1. Kir4.1Ϫ/Ϫ mice display marked motor impairment, and the cellular basis is hypomyelination in the spinal cord, accompanied by severe spongiform vacuolation, axonal swellings, and degeneration. Immunostaining in the spinal cord of wild-type mice up to postnatal day 18 reveals that Kir4.1 is expressed in myelin-synthesizing oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
310
1
21

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(359 citation statements)
references
References 40 publications
27
310
1
21
Order By: Relevance
“…Deletion of Kirs in mouse models has been shown to cause hypomyelination of white matter structures mimicking leukodystrophy, which is supportive with the multiple periventricular hyperdense lesions in our patient. 15 In our study, we found that the KCNJ2 T192I mutation is the genetic cause of ATS in our index family. T192I is located on the highly conserved region of the C-terminal intracellular domain of the Kir2.1 protein (Figure 1e), highlighting the importance of this residue in the evolution.…”
Section: Discussionmentioning
confidence: 52%
“…Deletion of Kirs in mouse models has been shown to cause hypomyelination of white matter structures mimicking leukodystrophy, which is supportive with the multiple periventricular hyperdense lesions in our patient. 15 In our study, we found that the KCNJ2 T192I mutation is the genetic cause of ATS in our index family. T192I is located on the highly conserved region of the C-terminal intracellular domain of the Kir2.1 protein (Figure 1e), highlighting the importance of this residue in the evolution.…”
Section: Discussionmentioning
confidence: 52%
“…Kir4.1 channel subunits, which conduct weakly inwardly rectifying currents in glia (Connors and Kofuji 2002;Kofuji and Newman 2004;Neusch et al 2006;Neusch et al 2001), have been suggested to play homeostatic roles within cochlear tissues (Hibino et al 1999;Hibino et al 1997;Marcus et al 2002;Rozengurt et al 2003;Takeuchi et al 2000). Consequently, we re-investigated the expression of Kir4.1 in the guinea pig cochlear lateral wall.…”
Section: Dye Transfer Reveals Intercellular Coupling and Tonotopic Vamentioning
confidence: 97%
“…5A and B), a blocker of currents carried by the K + channel subunit Kir4.1 in glia (Connors and Kofuji 2002;Neusch et al 2006;Neusch et al 2001). Application of Ba 2+ also caused depolarization of root cells ( Fig.…”
Section: Dye Transfer Reveals Intercellular Coupling and Tonotopic Vamentioning
confidence: 99%
“…Global knockout of Kir4.1 leads to postnatal lethality (Neusch, Rozengurt, Jacobs, Lester, & Kofuji, 2001), whereas conditional Kir4.1 knockout in astrocytes alone is able to trigger epilepsy (Chever, Djukic, McCarthy, & Amzica, 2010; Haj‐Yasein et al, 2011a). In the same vein, mutations or single nucleotide polymorphisms in the genes encoding Kir4.1 are associated with human epilepsy (Bedner and Steinhauser.…”
Section: Astrocytes In the Diseased Brain Are Central To Neuropathologymentioning
confidence: 99%